The effect of different genotype cattle grazing on the nutrient content of saline grasslands vegetation - Kovácsné Koncz, Nóra; Simon, Ádám; Béri, Béla (Acta Agraria Debreceniensis, 2018)
Maintaining saline grasslands in good condition, preserving their yield and diversity is important not only for the purpose of nature conservation, but also for farming. Therefore, the primary purpose of our study is to analyse the effect of pasture use of the smaller weight extensive and the larger weight intensive beef cattle on the grassland vegetation and nutrient content. In this way, we can answer the question whether grazing for nature conservation can be achieved with more profitable, more economical and more intense varieties.The tests were carried out in May 2016 and May 2017, in the Hortobágy National Park (Pap-ere and Zám puszta), where a total of 16 sample areas were analysed. These areas are grazed with extensive beef cattle (Hungarian grey) and mixed genotype of intensive cattle. The associations were selected along a moisture gradient, such as wet salt marsh (Bolboschoenetum maritimi) and drier saline meadow (Beckmannion eruciformis). All the vegetative material collected both years in May was analysed for the following parameters: dry matter, crude protein, crude fibre and life-sustaining net energy content. We compared the effects of medium grazing (0.46 livestock/ha) and abandonment on vegetation and nutrient content.We examined the effect of (i) grazing, (ii) different grasslands (salt marsh, saline meadow) and (iii) grazing of different cattle breeds (Hungarian grey, intensive beef) on the nutrient content of the vegetation of grasslands Based on our results, it was found that grazing had an impact on crude protein and life-sustaining net energy content. The highest crude protein content (12.75 m/m%) was obtained in the year 2017 in the area where higher density had been grazed for two years. For the lifesustaining net energy, the highest value (5.05 MJ/kg d.m.) was also obtained in 2017 and the lowest in 2016. Furthermore, it was found that there was no significant difference between the effect of the two cattle breeds on the parameters examined. Significant effects were observed only in the case of life-sustaining net energy: in the area of intensive beef cattle we received a higher value (5.15 MJ/kg body weight) than in the area with extensive beef cattle (4.96 MJ/kg body weight).Our results have also shown that cattle grazing is of the utmost importance for the maintenance of both wet and mesophilous habitats. Based on our three-year study, we can say that grazing by both extensive and intensive cattle breeds is suitable for the management of saline habitats.